Neuromuscular fatigue in racquet sports - Girard, O.; Millet, G. P. (Physical Medicine & Rehabilitation Clinics of North America, 2008)
This article describes the physiologic and neural mechanisms that cause neuromuscular fatigue in racquet sports: table tennis, tennis, squash, and badminton. In these intermittent and dual activities, performance may be limited as a match progresses because of a reduced central activation, linked to changes in neurotransmitter concentration or in response to afferent sensory feedback. Alternatively, modulation of spinal loop properties may occur because of changes in metabolic or mechanical properties within the muscle. Finally, increased fatigue manifested by mistimed strokes, lower speed, and altered on-court movements may be caused by ionic disturbances and impairments in excitation-contraction coupling properties. These alterations in neuromuscular function contribute to decrease in racquet sports performance observed under fatigue.